ARTIFICIAL INTELLIGENCE AND MARKETING INTERSECTION POST-COVID-19: A CONCEPTUAL FRAMEWORK - Shoucheng Zhang, (International Journal of Innovative Technologies in Social Science, 2022)
As a result of mass digitization during the pandemic, businesses were able to automate business processes, giving people and brands a deeper connection. A proactive strategy, however, is the next step for organizations to implement AI during crisis situations by going one step further. In spite of this, most organizations still do not adequately address this growing problem. After Covid outbreaks, consumer behavior is unlikely to return to pre-pandemic levels. Consumers will increasingly buy goods and services online, and more people will work remotely. In the post-Covid-19 world, as economies slowly begin to open up again, artificial intelligence (AI) will be extremely valuable as companies begin to adapt to the new environment. Similar to other global crises, several major trends that were already underway before Covid are likely to accelerate as a result of the pandemic. Companies must continue to invest in artificial intelligence initiatives during the recovery phase. A conceptual framework for marketing and user engagement is presented in this paper that uses artificial intelligence and automation in ways that are user-centric, integrating traditional marketing practices into an overarching framework that can be implemented by structured artificial intelligence. Embedded technologies, artificial intelligence, and automation have had a significant impact on the four Ps of marketing and will continue to do so.